Cryptosporidium rubeyi n. sp. (Apicomplexa: Cryptosporidiidae) in multiple Spermophilus ground squirrel species. Issue 3 (December 2015) - Li, Xunde; Pereira, Maria das Graças Cabral; Larsen, Royce; Xiao, Chengling; Phillips, Ralph; Striby, Karl; McCowan, Brenda; Atwill, Edward R.
Abstract: Previously we reported the unique Cryptosporidium sp. "c" genotype (e.g., Sbey03c, Sbey05c, Sbld05c, Sltl05c) from three species of Spermophilus ground squirrel ( Spermophilus beecheyi, Spermophilus beldingi, Spermophilus lateralis ) located throughout California, USA. This follow-up work characterizes the morphology and animal infectivity of this novel genotype as the final step in proposing it as a new species of Cryptosporidium . Analysis of sequences of 18S rRNA, actin, and HSP70 genes of additional Cryptosporidium isolates from recently sampled California ground squirrels ( S. beecheyi ) confirms the presence of the unique Sbey-c genotype in S. beecheyi . Phylogenetic and BLAST analysis indicates that the c-genotype in Spermophilus ground squirrels is distinct from Cryptosporidium species/genotypes from other host species currently available in GenBank. We propose to name this c-genotype found in Spermophilus ground squirrels as Cryptosporidium rubeyi n. sp. The mean size of C. rubeyi n. sp. oocysts is 4.67 (4.4–5.0) μm × 4.34 (4.0–5.0) μm, with a length/width index of 1.08 (n = 220). Oocysts of C. rubeyi n. sp. are not infectious to neonatal BALB/c mice and Holstein calves. GenBank accession numbers for C. rubeyi n. sp. are DQ295012, AY462233, and KM010224 for the 18S rRNA gene, KM010227 for the actin gene, and KM010229 for the HSP70 gene. Graphical abstract: Highlights: Cryptosporidium rubeyi is a newly described species of Cryptosporidium . C. rubeyi is isolated from Spermophilus ground squirrels from California, USA. C. rubeyi demonstrates host specificity given it is not infectious for mice or calves.